EPIDEMIOLOGY OF HYPERTENSION AMONG PATIENTS ON HEMODIALYSIS AND THE SIGNIFICANCE OF VOLUME OVERLOAD. (April 2021) - Tsikliras, N.; Georgianos, P.; Karpetas, A.; Minasidis, E.; Syrganis, C.H.; Anagnostara, A.; Chatzidimitriou, C.; Pikilidou, M.; Liakopoulos, V.; Zebekakis, P.; Balaskas, E.
Abstract : Objective: Earlier cross-sectional studies provided variable estimates of the prevalence and control of hypertension among patients on hemodialysis due to their heterogeneity in definitions and because they were based mainly on routine blood pressure (BP) recordings obtained within the dialysis-unit. The aim of the present study was to explore the epidemiology of hypertension in hemodialysis using home BP monitoring (HBPM). Design and method: A total of 120 prevalent hemodialysis patients underwent HBPM over 1 week with the validated automatic device HEM-705 CP (Omron, Healthcare). BP was recorded 3 times daily — on awaking up, between noon and at bedtime. The volume status of participants was assessed via bioelectrical-impendence-analysis (BIA) after the completion of the mid-week dialysis session using the BCM monitor (Fresenius Medical Care, Germany). Results: Hypertension (defined as 1-week averaged home BP higher than 135/85 mmHg or current use of antihypertensive medications) was detected in 88.8% of participants. Although 92.2% of hypertensives were being treated with an average of 2.0 BP-lowering medications, adequate control of home BP was achieved in only 32.6%. In multivariate logistic regression analysis, compared with those participants not receiving antihypertensive treatment (reference category), the odds ratio (OR) for uncontrolled hypertension was 3.15 for those receiving 1 antihypertensive, 3.85 for those receiving 2 antihypertensives and 18.1 for those receiving above 3 antihypertensives (P = 0.028 for the interaction). Each 1 L higher postdialysis overhydration was associated with 1.72 higher OR for uncontrolled home BP (P = 0.002). Conclusions: Hypertension in hemodialysis diagnosed by HBPM is highly prevalent and remains poorly controlled. Excessive antihypertensive drug use and extracellular volume expansion appear to be the strongest determinants of inadequate BP control in this population.